1981
DOI: 10.1002/ana.410100611
|View full text |Cite
|
Sign up to set email alerts
|

The origin of spontaneous electrical activity at the end‐plate zone

Abstract: Two types of spontaneous electrical activity are present at the end-plate zone: low-voltage negative potentials that correspond to miniature end-plate potentials, and larger voltage negative-positive potentials. The electrogenic origin of the latter has been uncertain. The origin of these larger potentials was investigated in the rat phrenic nerve diaphragm preparation and in human gastrocnemius muscle just prior to intubation during administration of preoperative anesthesia. In the hemidiaphragm the larger vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 6 publications
0
24
0
3
Order By: Relevance
“…Moreover the waveform of the noise in active trigger points was consistent with motor endplate and not muscle spindle activity [27]. Traditionally, electrophysiological recordings of end plate noise consist of endplate potentials, caused by spontaneous ACh release from neuromuscular junctions, and end plate spikes, the result of needle irritation of the neuromuscular junction [22,28,29]. However, more recent studies suggest that the electrical noise is produced by extrafusal neuromuscular junctions, while the combination of noise and spikes demonstrates intrafusal activity in the vicinity of the motor endplates [22].…”
Section: The Physiology Of Pain Related To Myofascial Trigger Pointsmentioning
confidence: 97%
“…Moreover the waveform of the noise in active trigger points was consistent with motor endplate and not muscle spindle activity [27]. Traditionally, electrophysiological recordings of end plate noise consist of endplate potentials, caused by spontaneous ACh release from neuromuscular junctions, and end plate spikes, the result of needle irritation of the neuromuscular junction [22,28,29]. However, more recent studies suggest that the electrical noise is produced by extrafusal neuromuscular junctions, while the combination of noise and spikes demonstrates intrafusal activity in the vicinity of the motor endplates [22].…”
Section: The Physiology Of Pain Related To Myofascial Trigger Pointsmentioning
confidence: 97%
“…The origin of end plate spikes is less clear. 9 One group suggests that they originate from within muscle spindles as muscle action potentials in intrafusal fibres. [10][11][12] However, it seems conceivable that they could be related to the combined effect of the simultaneous release of two or three vesicles of ACh on the excitatory post-synaptic potentials.…”
mentioning
confidence: 99%
“…Buchthal and Rosenfalck [6] observed that miniature end plate potentials (MEPPs), or end plate noise, were often associated with this activity, which they called 'spontaneous diphasic spikes'. Finally, Brown and Varkey [7] proved that 'nerve potentials' were postsynaptic, recorded from muscle fibres. Thereafter, the term 'nerve potentials' was rejected and at present these potentials are called 'end plate spikes' (EPSs).…”
Section: Muscle Pain Produced By a Needle During Needle Electromyographymentioning
confidence: 99%